Multiproxy sediment provenance analysis of two megafans in the Owambo Basin, northern Namibia. Issue 2 (2023) - Gärtner, Andreas; Houben, Georg J.; Sitnikova, Maria A.; Miller, Roy McG; Wang, Feiyu; Zieger-Hofmann, Mandy; Zieger, Johannes; Linnemann, Ulf
No abstract available